A collated overview on the evaporative cooling applications for photovoltaic modules - Cengiz, Mazlum; Kayri, Ismail; Aydin, Huseyin (Pergamon-Elsevier Science Ltd, 2024)
Cooling of photovoltaic modules is a crucial subject because it recovers and improves the module's electrical efficiency, power output, and lifetime, especially in hot and arid climates. Thus, different cooling methods have been innovated and investigated in many studies. Evaporative cooling is one of these applied methods, holding a great potential for managing the temperature of the modules especially installed in hot and dry lands. This study aims to inform researchers about current techniques which have been employed for evaporative cooling systems for PV modules. Moreover, it is the first review on evaporative cooling systems for photovoltaic modules. This review study highlights that existing evaporative systems mainly consist of techniques such as absorbent pads, synthetic clay, zeolite, phase change layers, co-current configurations, droplet evaporation, PV evaporative chimney, chimney-like channels, atmospheric water harvester and the heat pipe thermosiphon. As the result of the interpretations of the collected literature, it can be said that some of these applications have a great potential in enhancing an overall performance of a PV system. The current evaporative systems appear to be environmentally friendly, inexpensive, and reliable. They mainly utilize water as a coolant. Besides, it is recommended that different chemicals with low boiling points can be evaluated as alternative coolants to water. Moreover, many other recommendations for future studies are suggested.
Keywords: Photovoltaics; Evaporative cooling; Solar cells; Heat removal; Electrical efficiency; Temperature reduction